2020
DOI: 10.1111/tbed.13616
|View full text |Cite
|
Sign up to set email alerts
|

Swine influenza viruses and pandemic H1N1‐2009 infection in pigs, Myanmar

Abstract: Swine influenza virus (SIV) is a segmented, enveloped, negative-sense, single-stranded RNA virus of the genus Alphainfluenzavirus. SIV is a highly contagious virus that causes swine influenza, a respiratory disease in pigs. SIV infection is characterized by fever, coughing, sneezing, nasal discharge, breathing difficulty and decreased appetite. SIV-infected pigs show clinical signs within 24 hr, with high morbidity but very low mortality. The transmission of SIVs could occur

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…We found that H1N1/pdm09 virus is circulating enzootically in Cambodian swine herds. Since the H1N1/2009 pandemic, multiple H1N1/pdm09 virus spillovers back to pigs have occurred, seeding novel H1N1 reassortant viruses across the world [37-39]. We also detected multiple reverse zoonotic H3 lineages in Cambodian pigs that had circulated undetected for about 10 years.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…We found that H1N1/pdm09 virus is circulating enzootically in Cambodian swine herds. Since the H1N1/2009 pandemic, multiple H1N1/pdm09 virus spillovers back to pigs have occurred, seeding novel H1N1 reassortant viruses across the world [37-39]. We also detected multiple reverse zoonotic H3 lineages in Cambodian pigs that had circulated undetected for about 10 years.…”
Section: Discussionmentioning
confidence: 87%
“…Multiple lineages of swIAV have been detected in pigs across Southeast Asia [12-18]. In Thailand, the H1N1/pdm09 virus was the prevailing subtype detected in swine from 2011 to 2014 [14], co-circulating with classical swine (CS) H1, EA H1N1, and H3N2 lineages [13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…All strains shared the following five glycosylation sites ( 28 NST 30 , 40 NVT 42 , 291 NCT 293 , 498NGT 500 , 557 NGS 559 ), while SW/198/20 had an additional glycosylation site at 502NYS504 compared to the other strains. The increase in glycosylation sites may be related to the strain's heightened pathogenicity ( Bourret, 2018 ; Mon et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%